The role of technology-based professional development in improving EFL teachers’ classroom practices - Elvina; Amanda Nurul Hidayah; Etna Gres; Yohanes Gatot Sutapa Yuliana; Dwi Riyanti (JL3T (Journal of Linguistics, Literature and Language Teaching), 2026)
This study addressed the persistent gap between English as Foreign Language teachers' participation in technology-based professional development and the sustained application of new skills in classroom practice. The research aimed to explore teachers’ experiences of technology-based professional development in terms of access, participation, perceived benefits, impacts, and challenges in applying acquired knowledge in EFL classroom practices. The study employed a mixed-methods survey design, collecting data from 23 active English teachers across various schooling levels in West Kalimantan, Indonesia. Data were gathered through an online-administered survey and analyzed using descriptive statistics for quantitative data and thematic analysis for qualitative data. The principal findings revealed that teachers were proactive and viewed professional development as a valuable resource for improving practical knowledge and building confidence. However, severe contextual barriers, such as insufficient infrastructure, limited student device access, and a lack of follow-up support, impeded consistent implementation. The study concludes that the effectiveness of technology-based professional development is highly dependent on contextual factors, particularly infrastructure limitations, unequal student access to devices, and the absence of sustained support. It highlights the need for professional development programs to move beyond one-time technical training toward continuous, context-sensitive models that equip teachers with practical strategies tailored to low-resource EFL classrooms.